A “Cookbook” for Vulnerability Research - Tallman, Paula S.; Valdés-Velásquez, Armando; Salmón-Mulanovich, Gabriela; Lee, Gwenyth O.; Riley-Powell, Amy R.; Blanco-Villafuerte, Luciana; Hartinger, Stella M.; Paz-Soldán, Valerie A. (Frontiers in Public Health, 2019)
There is a growing need to facilitate the interdisciplinary study of the relationship between the environment and human health and well-being. It is increasingly recognized that vulnerability is a key construct allowing discipline-specific research questions on these topics to be meaningfully contextualized. However, there is little consensus regarding the meaning of the concept of vulnerability or how it can best be utilized in research studies. In this perspective article, we use the metaphor of a “cookbook” to review promising trends in vulnerability research and to make this body of research accessible to a multi-disciplinary audience. Specifically, we discuss a selection of “recipes” (theoretical frameworks), “ingredients” (vulnerability domains), “cooking tools” (qualitative and quantitative methods), and approaches to “meal presentation” (communication of results) drawn from vulnerability studies published in the past 15 years. Our aim is for this short “cookbook” to serve as a jumping-off point for scholars unfamiliar with the vulnerability literature and an inspiration for scholars more familiar with this topic to develop new ways to navigate the tension between locally-specific assessments of vulnerability and attempts at standardization. Our ultimate take-home message is that the specifics theories and methods used in vulnerability research are less important than attention to what we see as the 3 ‘T’s of transparency, triangulation, and transferability, and to efforts to make vulnerability research both “place-based” and comparable.